The Response of a Baroclinic Anticyclonic Eddy to Relative Wind Stress Forcing - Wilder, Thomas; Zhai, Xiaoming; Munday, David; Joshi, Manoj (Journal of physical oceanography, 2022)
Including the ocean surface current in the calculation of wind stress is known to damp mesoscale eddies through a negative wind power input and have potential ramifications for eddy longevity. Here, we study the spindown of a baroclinic anticyclonic eddy subject to absolute (no ocean surface current) and relative (including ocean surface current) wind stress forcing by employing an idealized high-resolution numerical model. Results from this study demonstrate that relative wind stress dissipates surface mean kinetic energy (MKE) and also generates additional vertical motions throughout the whole water column via Ekman pumping. Wind stress curl–induced Ekman pumping generates additional baroclinic conversion (mean potential to mean kinetic energy) that is found to offset the damping of surface MKE by increasing deep MKE. A scaling analysis of relative wind stress–induced baroclinic conversion and relative wind stress damping confirms these numerical findings, showing that additional energy conversion counteracts relative wind stress damping. What is more, wind stress curl–induced Ekman pumping is found to modify surface potential vorticity gradients that lead to an earlier destabilization of the eddy. Therefore, the onset of eddy instabilities and eventual eddy decay takes place on a shorter time scale in the simulation with relative wind stress.